The use of ICTs for the training of health professionals - Godoy, Solange Cervinho Bicalho (2019)
The accumulated experience with the incorporation of ICTs present a high resolubility. Objective: This study aimed to report the experience with the training process for health professionals mediated by ICTs in Portugal and Brazil. Method: He carried out the implementation of a training for the nurses inserted in the Hospital of Braga / Braga / Portugal with the participation of pro- fessors of the Federal University of Minas Gerais / Brazil, using the ICTs. Results: The evaluation of experience and analysis of the reference framework allowed us to understand that distance education (DLE) presents itself as a possibility for the democratization of knowledge for health professionals, serving as a strategy that assists in decision-making in the day-to-day health care. ICT is an important tool in the process of work and permanent education, making it a learning-work possibility that happens in the daily lives of people and organizations. Conclusion: The process of training health professionals should be based on the problems of praxis, considering the knowledge and experiences that people bring in their professional experience.